2019
DOI: 10.1177/0898264318822238
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation Among Adults Aging With Long-Term Physical Disability: The Role of Socioenvironmental Factors

Abstract: Objective: This study examined the environmental barriers and facilitators that hinder or promote participation among adults aging with physical disabilities. Method: Data come from an ongoing study of 1,331 individuals aging with long-term physical disability ( M = 65 years). Linear regression examined the association between individual and socioenvironmental factors and participation restrictions in work, leisure, and social activities. Results: Pain, fatigue, and physical functional limitations were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 72 publications
2
16
0
1
Order By: Relevance
“…This may be reflective of proactive steps taken by people with milder OA to maintain activity and social engagement. In a study of midlife to older adults with a range of long‐term physical health conditions, Clarke et al showed that those with a greater number of years since diagnosis had somewhat greater participation and suggested that this was due to coping or adaptation strategies learned over time (38). Unfortunately, OA disease duration was not available for our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be reflective of proactive steps taken by people with milder OA to maintain activity and social engagement. In a study of midlife to older adults with a range of long‐term physical health conditions, Clarke et al showed that those with a greater number of years since diagnosis had somewhat greater participation and suggested that this was due to coping or adaptation strategies learned over time (38). Unfortunately, OA disease duration was not available for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, OA disease duration was not available for our study. Clarke et al also reported that those individuals with higher levels of perceived social supports reported greater ability to participate in social roles and activities (38). As the participation measure used in the study by Clarke and colleagues most closely aligned with our social participation–intensity indicator, their findings support those revealed in our study, linking the perceived availability of instrumental support with social participation–intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Antecedents of participation from across the fields of literature can also be summarized as factors related to the person or the context. Person-related antecedents include interest or willingness to take part [54], and past satisfaction [64], as well as antecedents that prevent participation, such as pain [64], depression, mood disorder [32], fatigue, or physical limitations [65]. Age was proposed to shape participation in that it influences capacity for choice.…”
Section: Antecedents and Consequences To Wellbeing And Participationmentioning
confidence: 99%
“…We had hypothesized that participants who self-reported activity limitations and those using mobility aids would be more vulnerable to barriers in the outdoor built environment. Given findings of previous research, we expected perceived sidewalk problems to be associated with less frequent neighborhood participation, particularly in those with underlying limitations in mobility function (Clarke et al, 2019). We did not observe interactions between severity of sidewalk problems and activity limitations.…”
Section: Discussionmentioning
confidence: 99%